2009
DOI: 10.3155/1047-3289.59.5.553
|View full text |Cite
|
Sign up to set email alerts
|

Energy Recycling by Co-Combustion of Coal and Recovered Paint Solids from Automobile Paint Operations

Abstract: Experiments were carried out in a pilot-scale pulverized coal combustor at the Energy and Environmental Research Center (EERC) burning a Powder River Basin (PRB) subbituminous coal. A scanning mobility particle sizer (SMPS) and an electrical low-pressure impactor (ELPI) were used to measure the particle size distributions (PSDs) in the range of 17 nm to 10 microm at the inlet and outlet of the electrostatic precipitator (ESP). At the ESP inlet, a high number concentration of ultrafine particles was found, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The standard deviation of the measurement was negligible, indicating a relatively constant aerosol property at the sampling location. For the results measured with a dryer (represented by white connected symbols), the particles had a mode diameter of 37.2 nm, a value similar to those found in previous studies on particle measurement in flue gas (Li et al 2009;Ylätalo and Hautanen 1998). The concentration of particles at 37.2 nm was 3.3 × 10 8 #/cm 3 .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The standard deviation of the measurement was negligible, indicating a relatively constant aerosol property at the sampling location. For the results measured with a dryer (represented by white connected symbols), the particles had a mode diameter of 37.2 nm, a value similar to those found in previous studies on particle measurement in flue gas (Li et al 2009;Ylätalo and Hautanen 1998). The concentration of particles at 37.2 nm was 3.3 × 10 8 #/cm 3 .…”
Section: Resultssupporting
confidence: 79%
“…Numerous studies have focused on measuring the concentration of fine particles before or after a particle control unit, such as an ESP or a bag-house filter, because it is typically the principal unit that causes the most significant variation in particle concentration in the exhaust. Li et al (2009) used a scanning mobility particle sizer (SMPS) and an electrical low-pressure impactor (ELPI) to measure the particle size distribution in the flue gas upstream and downstream of a pilot-scale ESP, and found that adding photoionizers (such as a soft x-ray [SXR]) could enhance the particle removal efficiency in the submicrometer range. Strand et al (2002) studied the effect of an ESP and condenser on the particle concentrations from 10 nm to 10 µm in the exhaust gas from a 6-MW biomass combustor.…”
Section: Introductionmentioning
confidence: 99%
“…The particle size distribution in the flue gas from PRB coal combustion is shown in Figure 7. The size distribution is typical for coal combustion Suriyawong et al, 2006;Li et al, 2009b;Wang et al, 2013b). Figure 7 also shows that the ESP can remove at least 99.7% of the fly ash particles.…”
Section: Effect Of Particles In Flue Gasmentioning
confidence: 81%
“…While emission sources such as power 52 plants (Li et al, 2009), airports (Hu et al, 2009), building demolition sites (Hansen et 53 al., 2008), tyre and road surface wear (Dahl et al, 2006), biofuel derived (Kumar et 54 al., 2010b), natural formation (Holmes, 2007) and other emerging sources such as 55 manufactured nanomaterials (Kumar et al, 2010a) are important contributors to the 56 number concentration of atmospheric particles, emissions from gasoline-and diesel-57 fuelled vehicles remain the dominant source in polluted urban environments. These 58 can alone contribute up to about 90% of the total particle number (ToN) 59…”
Section: Introduction 49mentioning
confidence: 99%